Cucurbitacin: Ancient Compound Shedding New Light on Cancer Treatment. (2010) - Lee, Dhong Hyun; Iwanski, Gabriela B.; Thoennissen, Nils H.
Abstract : Cucurbitacins and their derivatives are triterpenoids found in medicinal plants known for their diverse pharmacological and biological activities, including anticancer effects, throughout human history. Although initial attention to cucurbitacin as a potential anticancer drug withered for decades, recent discoveries showing that cucurbitacin is a strong STAT3 (Signal Transducers and Activators of Transcription-3) inhibitor have reclaimed the attention of the drug industry one more time. There is increasing evidence showing that some cucurbitacins not only inhibit the JAK-STAT pathway, but also affect other signaling pathways, such as the MAPK pathway, which are also known to be important for cancer cell proliferation and survival. Moreover, some reports have shown the synergistic effect of cucurbitacins with known chemotherapeutic agents, such as doxorubicin and gemcitabine. In this review, we will summarize the recent discoveries regarding molecular mechanisms of action of cucurbitacins in human cancer cells and discuss the possibilities of cucurbitacin as a future anticancer drug in clinical settings.